Improved optical generalized spatial modulation in Málaga turbulent channel - Hui ZHAO; Weiwen MA; Jin LI; Wenchao DENG; Hui WAN; Tianqi ZHANG; Yuanni LIU (Tongxin xuebao)
Aiming at the problems of space resource waste and error bit performance limitation caused by fixed optical antenna combination set used in traditional optical generalized spatial modulation (OGSM), an improved scheme based on low complexity adaptive optical antenna combination set selection algorithm was proposed.First, the Euclidean distance matrix between optical antenna combinations was calculated using channel state information.Then, based on the principle of Euclidean distance equivalence and the idea of maximum norm antenna selection, the optical antenna combination with poor channel state was deleted, and the final reserved optical antenna combination was the optimal optical antenna combination set in the current state.The traversal of all optical antenna combinations was avoided and the complexity of the algorithm was reduced to a large extent.The simulation results show that the BER performance of the improved OGSM scheme outperforms the conventional OGSM under different conditions.